Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.1161/circresaha.122.321923
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic Signatures Associated With Pulmonary Arterial Hypertension Outcomes

Abstract: Background: Pulmonary arterial hypertension (PAH) is a complex disease characterized by progressive right ventricular (RV) failure leading to significant morbidity and mortality. Investigating metabolic features and pathways associated with RV dilation, mortality, and measures of disease severity can provide insight into molecular mechanisms, identify subphenotypes, and suggest potential therapeutic targets. Methods: We collected data from a prospective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 55 publications
0
10
0
Order By: Relevance
“…The lipid profile of obesity identified in this study has previously been found to predict the development of hypertension risk, diabetes, and insulin resistance (53)(54)(55). Consistent with prior studies, our findings demonstrate that the OMS constructed from obesity-based differential metabolites, three of which were welldistributed in the lipid metabolism (thymidine, SM d40:1, Llysinamide), was strongly correlated with developing hypertension risk and positively correlated with systolic blood pressure, but it did not demonstrate a similar relationship with diastolic blood pressure, which was also an interesting finding.…”
mentioning
confidence: 64%
“…The lipid profile of obesity identified in this study has previously been found to predict the development of hypertension risk, diabetes, and insulin resistance (53)(54)(55). Consistent with prior studies, our findings demonstrate that the OMS constructed from obesity-based differential metabolites, three of which were welldistributed in the lipid metabolism (thymidine, SM d40:1, Llysinamide), was strongly correlated with developing hypertension risk and positively correlated with systolic blood pressure, but it did not demonstrate a similar relationship with diastolic blood pressure, which was also an interesting finding.…”
mentioning
confidence: 64%
“…Spanning over two decades, extensive basic, translational, and clinical analyses have supported a causative link between metabolic reprogramming and PAH 28,29 . Similar to the Warburg effect in cancer, a shift from mitochondrial oxidation to glycolysis appears to occur in the right ventricle of PAH patients 22,23 .…”
Section: Discussionmentioning
confidence: 99%
“…We included adult participants from a singleinstitution PAH cohort. 4 Participants provided informed consent and the University of Washington Institutional Review Board approved the study (#3387). Participants were diagnosed with PAH using the standard definition at the time of enrollment, had PAH diagnosed after age 20, and were followed for up to 3 years or until death.…”
Section: Methodsmentioning
confidence: 99%